Attempts at the ultrasonic visualization of the heart in real time - FILIPCZYŃSKI, Leszek; SAŁKOWSKI, Jan (Archives of Acoustics, 1977)
In recent years several papers have been published aimed at the visualization of the heart by means of an ultrasonic method giving a geometrical picture of the distribution of tissues in a selected area of examination.